Gambaran Upaya Awal Pengelolaan Kecemasan Pada Pasien Gagal Ginjal Kronis Di RSU Yarsi Pontianak - Ali Akbar; Mimi Amaludin; Nurpratiwi Nurpratiwi; Uti Rusdian Hidayat; Fauzan Alfikrie; Debby Hatmalyakin (Universitas Malahayati Lampung, 2022)
ABSTRACT In chronic kidney failure (CKD), the kidneys can lose their role and function progressively and irreversibly. Efforts made by CKD patients with hemodialysis therapy still leave quite a serious problem for CKD patients, especially in the psychological aspect, namely anxiety. This study aims to describe an independent effort to manage anxiety in patients with chronic kidney failure. Design in analytical descriptive research. This research was conducted at YARSI Pontianak General Hospital. The population of this study was 61 patients undergoing hemodialysis at the Yarsi General Hospital in Pontianak for the period of May 2021. This study uses total sampling so that the entire population will be the sample. The instrument of this research used a questionnaire. Initial efforts to manage anxiety in patients with chronic kidney failure performed deep breathing as many as 36 people (59%), muscle relaxation totaled 12 people (19.7%), exercise amounted to 2 people (3.3%), meditation amounted to 31 people (50 people). ,8%), mental imagination is 4 people (6.6%), positive thinking is 44 people (72.1%). Where respondents on average make more than one effort in managing anxiety. Respondents on average made more than one effort in managing anxiety. Keywords: Chronic Kidney Failure, Self-Effort, Anxiety Management ABSTRAK Pada kondisi gagal ginjal kronis (GGK), ginjal dapat mengalami kehilangan peran dan fungsinya secara progresif dan irreversibel. Upaya yang dilakukan pasien GGK dengan terapi hemodialisa ternyata masih menyisakan masalah yang cukup serius bagi pasien GGK terutama pada aspek psikologis yaitu kecemasan. Penelitian ini bertujuan untuk melihat gambaran upaya mandiri pengelolaan kecemasan pada pasien gagal ginjal kronis. Desain pada penelitian deksriptif analitik. Penelitian ini dilaksanakan di Rumah Sakit Umum YARSI Pontiank. Populasi penelitian ini adalah pasien yang menjalani hemodialisa di RSU Yarsi Pontianak periode bulan Mei 2021 berjumlah 61 orang. Penelitian ini menggunakan total sampling sehingga seluruh populasi akan menjadi sampel. Instrumen penelitian ini menggunakan kuesioner. Upaya awal pengelolaan kecemasan pada pasien gagal ginjal kronis melakukan tarik nafas dalam berjumlah 36 orang (59%), relaksasi otot berjumlah 12 orang (19,7%), olahraga berjumlah 2 orang (3,3%), meditasi berjumlah 31 orang (50,8%), imajinasi mental berjumah 4 orang (6,6%), berfikir positif 44 orang (72,1%). Dimana responden rata-rata melakukan lebih dari satu upaya dalam pengelolaan kecemasan. Responden rata-rata melakukan lebih dari satu upaya dalam pengelolaan kecemasan. Kata kunci: Gagal Ginjal Kronis, Upaya Mandiri, Pengelolaan Kecemasan